Restoration strategies in boreal forests - Espinosa Del Alba, Clara (2020)
The boreal biome is one of the largest in the world and their forests have been widely exploited for centuries. Consequently, it has suffered ecological simplification and loss of biodiversity. Under these circumstances passive conservation is no longer enough and active restoration techniques need to be tested. I evaluated short- and long-term effects of two restoration methods aimed to increase ecosystem structural variability. I focused on the responses of two organism groups: vascular plants in the field layer and bryophytes in the ground layer. A before-after control-impact study design was applied. It consisted of 18 voluntary set-asides in northern Sweden; each assigned to one of three treatments: prescribed restoration burning, gap cutting and untreated stands. Data was collected in three occasions: once prior to restoration (2010) and twice post restoration; one year after (2012) and eight years after (2019). I analysed the differences in two diversity measures (richness and Shannon Diversity) with linear mixed effect models and community composition changes with multivariate methods. My results showed that fire treatment caused an initial decline in diversity for both field and ground layer. However, in the long-term the field layer recovered and surpassed the diversity values present in the area before restoration. Ground layer did not show any sign of recovery. Community composition in burned stands differed significantly between each time point as well as when compared to other treatments, for both layers. By contrast, I found no significant differences in diversity measures or community composition due to gap cutting. The restoration methods tested in this study displayed some divergent results. Prescribed burning generated opposite responses depending on time since restoration for vascular plants in the field layer. However, it was found consistently detrimental in the ground layer and therefore not to recommend when bryophytes are the target species. The absence of effects from gap cutting can be understood as that minor changes in canopy cover does not affect the vegetation structure of forest stands. My study highlights the importance of including more than one organism group, different restoration methodologies and long-term studies in order to properly asses restoration outcomes at landscape level.